The Affect of Crafting : Third Millennium BCE Copper Arrowheads from Ganeshwar, Rajasthan. - Rizvi, Uzma Z. (Archaeopress archaeology., 2018)
The Affect of Crafting' presents an interrogation of materiality and crafting, a consideration of the situatedness of the technological practice of crafting itself, and the forms of relationships that exist between all things transformed in the act of crafting: bodies, minerals and landscapes.